PRECLINICAL RESEARCHES OF STEROID GLYCOSIDES OF Atropa belladonna L.SEEDS - Natalia Vladimirovna Latcerds (Современная наука и инновации)
Article is devoted to chemical pharmacological studying of Atropa belladonna L seeds, to identification of Atropa belladonna using possibility as a source of receiving biologically active connections. As a result of the carried-out researches it is established that the belladonna ordinary is a rich source of steroid glycosides. Atropozida showed gipocholesterinemic and antioxidant activity in preclinical researches.